Proyecto de implementación de un área recreativa que promueva el dominio corporal dinámico en el Taller Mundo Feliz del proyecto social Padre Juan Botasso en niños de 3 - 5 años - Castro Biedermann, María Elizabeth (2015)
This paper aims grade equip the Children's Centre Happy World Social Project Juan Botasso, recreational physical space with the resources to develop in children aged 3-5 years Dynamic Domain Corporal, posing for investigation analysis of the skills of young children of that institution and recognition of physical spaces. The study started from the literature review of various contributions on psychomotor including Piaget, Jiménez, Arguello, Freud, Lapierre and Aucouturier, Wallon among others; has been considered the guidelines given by Wallon for being the father of the psychomotor, who defines it as intimate relationship between physiological maturities and intellectual that occurs in every human being. It has been carried out field research in that institution, being able to identify the lack of knowledge of caretakers of young children on topics related to psychomotor and dynamic domino body and the absence of outdoor learning resources for development toddlers. The results of the research have generated the need to create a recreational area that allows toddlers develop these skills, so we can conclude that the psychomotor plays an important role in the harmonious development of the child's personality and girls from 3 to five years, since it allows the maturity of their motor skills, as well as establishing interactions at the level of thought, emotions and socialization.